Green Synthesis of Cu–ZnO Nanocomposite Using Pomegranate Peel Mesocarp Extract for Controlling Xanthomonas Campestris Causing Bacterial Blight in Tomato (Advances in Applied Biological Research, 2026)
Zinc oxide/copper (ZnO/Cu) nanoparticles were synthesized using a green  synthesis method based on pomegranate pulp peel extract. The purpose of the  study is to manufacture an environmentally friendly zinc and copper oxide  nanocomposite using plant residues from pomegranate pulp peel extract, and  to use it to combat bacterial blight in tomatoes. The synthesized sample was  examined to characterize the nanoparticles using UV-Vis spectroscopy, energy  dispersive spectroscopy (EDS), field-emission scanning electron microscopy (FE SEM), and X-ray diffraction (XRD).The observed peak at 480 nm in the surface  plasmon resonance of the zinc oxide nanoparticles indicated the formation of  nanoparticles of varying sizes, both large and small. The successful synthesis of  the compound was inferred from the shift in the UV-Vis absorption peaks using  pH, time, concentration, copper-to-zinc oxide ratio, and temperature. X-ray  diffraction (XRD) and phase morphology analysis revealed the crystalline nature  of the nanoparticles. The average crystal size of the ZnO nanoparticles synthesized  using the extract and ZnO/Cu nanocomposites was 24.16 nm, representing the  highest point in the halo. However, this is not considered a sharp “crystalline  peak,” and the presence of sharp peaks at angles of 25.85, 29.45, and 31.85 is  strong evidence of a regular atomic arrangement. Morphological analysis of the  synthesized nanoparticles using high-resolution electron microscopy (HR-TEM)  revealed an irregular to nearly spherical shape with sizes ranging from 10 to 200  nm.
Keywords: Green synthesis , Cu– ZnO Nanocomposite, Pomegranate Peel Mesocarp ,Xanthomonas Campestris ,Bacterial Blight Tomato